Bahasa Arab yang Dipelajari : (Ciri Khusus Bahasa Arab, Gaya Bahasa Lisan dan Tulisan, Fungsi dan Manfaat Komunikasi Bahasa Arab di Indonesia) - Azzahra Emira Sudrajat; Ummu Salamah; Ubaid Ridlo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This discussion outlines the general and specific characteristics of the Arabic language, including its phonological, morphological, and syntactic features. It also examines the distinction between spoken (‘ammiyyah) and written (fuṣḥā) forms of Arabic, as well as its strategic functions in Indonesia—such as serving as a means to understand Islamic teachings, strengthen religious education, facilitate da‘wah, and support diplomatic, economic, and cultural communication. Arabic provides significant benefits for Indonesian society, ranging from reinforcing religious identity to enhancing cognitive and multilingual abilities. Overall, Arabic holds substantial religious, academic, and social value across various aspects of life.